Legal framework on special education for children with disabilities: position in Malaysia and China - Noor Afiqah Ismail,; Nandni Arumugam,; Li, TingTing (Penerbit Universiti Kebangsaan Malaysia, 2023)
Education is crucial for all children, including those with disabilities, since it helps them become better citizens and ensures a prosperous future. Through a variety of declarations and treaties, the United Nations has recognised the right to education. In Malaysia, however, despite the fact that children with disabilities are offered the same educational rights as other children, it is still a grey area because the existing regulations regarding special education for children with disabilities are too vague. Therefore, the purpose of this research is to identify whether the existing laws in Malaysia are sufficient to protect the educational rights of children with disabilities. This research adopts doctrinal analysis, which helped researchers uncover educational rights issues for children with disabilities in Malaysia and comprehend doctrinal substance, including legislation and regulations, enforcement, and administration of special education in Malaysia. Comparative legal research was also adopted to determine which State, Malaysia or China has better laws regarding children with disabilities rights to education. It is found that China is more progressive in terms of its laws regarding special education. This research recommends that by modifying existing legislation and enhancing the school system for children with disabilities, their educational rights can be properly preserved.